Transcriptomic Analysis and Time to Hatch Visual Prediction of Embryo Development in the Ornate Spiny Lobster (Panulirus ornatus) - Lewis, Courtney L.; Fitzgibbon, Quinn P.; Smith, Gregory G.; Elizur, Abigail; Ventura, Tomer (Frontiers in Marine Science, 2022)
The ability to conduct closed life-cycle culture of tropical spiny lobsters, Panulirus ornatus, at the Institute for Marine and Antarctic Studies (IMAS) provides a unique opportunity to investigate specific developmental stages during embryogenesis. The production of closed life-cycle lobsters provides access to embryos at defined time points, yet physical staging is challenging due to their small size and environmental factors impacting their development. A transcriptome comprising 11 distinct stages across the 30-day P. ornatus embryonal development period allowed the establishment of the most detailed transcriptomic library of embryogenesis across decapods. A series of key genes across the 11 stages of embryonal development were characterized. The expression of neuropeptides was reported across P. ornatus embryos, suggesting they are primarily active during the later stages of embryogenesis as the nervous system develops and the animal prepares to hatch. Gastrula-specific genes, nanos and brachyury, presented an expression profile indicating gastrulation occurs early in embryogenesis. In addition to the molecular tools used to characterize embryo development, certain developmental characteristics, such as eye spot development, provide a measurable indicator that can be visualised. Hatch prediction models based on visual characteristics were shown to be an accurate method to predict the timing of the hatch for P. ornatus embryos kept at 26°C. The combination of morphological and visual measures with transcriptomics can be used to further define and establish the groundwork for future characterisation and staging of P. ornatus embryogenesis.